Implementation of Acute Flaccid Paralysis Surveillance in Emilia-Romagna, Italy: 2018-2019 analysis. (30th September 2020) - Morgado, M; Palandri, L; Colucci, M E; Affanni, P; Zoni, R; Pasquarella, C; Righi, E; Veronesi, L
Abstract: Problem: Acute flaccid paralysis (AFP) active surveillance is the gold standard in polio eradication process. Italy was classified in 2017 at intermediate risk of poliovirus reintroduction based on suboptimal poliovirus surveillance. The aim of this study was to restore an adequate level of AFP surveillance in Emilia-Romagna Region. Description of the Problem: The Emilia-Romagna's Reference Centre for AFP surveillance, in collaboration with the regional Public Health Service identified a collaborative network for AFP Surveillance by analysing the 2015-2017 Hospital Discharge Registers in all region's hospitals. The surveillance protocol was reviewed with the development of a computerized system of Active Surveillance-Zero Reporting sent by e-mail to doctors in the network every 15 days since October 2018. The goal was to restore the AFP notification system to meet WHO requirements sensitivity, completeness of case investigation, completeness of follow-up and to monitor the active surveillance program adherence. Results: The active surveillance network was composed by 49 doctors from both hospital administrations and clinical wards from 4 University Hospitals and 7 Local Health Authorities throughout the region. By the end of 2019, the mean response to each e-mail was 48.5% (SD 7.5%); 7 AFP cases have been reported; 85.7% received a full clinical and virological investigation and 83.3% completed the 60 day's follow-up. The final diagnosis of the cases was: 3 Guillain-Barre, 1 transient polyneuritis after HAV vaccination, 1 neuromyopathy from chronic disease, 1 acute myelitis in patient with DADA2. In 2 cases the paralysis persisted after 60 days. Lessons: In 2019, the active surveillance system reached sensitivity, completeness of case investigation and follow-up required. Intervention had no expenses, is easily reproducible, created a direct collaboration between clinical colleagues in the network and the reference center which restored adherence to AFP surveillance. Key messages: This work proposes how to improve AFP surveillance in a setting with low polio risk perception due to the absence of cases. Additionally, it reinforces the importance of direct collaboration/teamwork between institutions, regional reference centres and clinicians.